Extended range of motion does not induce greater muscle damage than conventional range of motion in the bench press exercise - Patryk Matykiewicz (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2023)
Introduction: Range of motion (ROM) of resistance exercise affects the muscle damage magnitude and the recovery-time course. Thus, the main aim of this study was to compare conventional and extended ROM in the bench press exercise on neuromuscular fatigue assessed by velocity changes during bench press throw, as well on the exercise-induced muscle damage evaluated by creatine kinase (CK) activity in the blood. Material and Methods: A total of fourteen healthy, well-trained males performed 5 sets of the bench press exercise at 70% of one repetition maximum with either standard (STD) and cambered (CMB) barbell until reaching volitional failure. CK and barbell velocity changes were assessed at the baseline and 1h, 24h, 48h post exercise protocol. Results: The results showed that higher peak barbell velocity was reached during the bench press throw after the CMB when compared to the STD condition. Moreover, CK activity showed an overall significant growing trend from baseline to time points following exercise during the STD, whereas the CMB post-48h CK was higher in comparison to pre and post, but not than post-24h. Conclusion: the bench press exercise performed with the use of CMB barbell might not require a specific training approach, and even higher training frequency might be applied.